Using the aquatic therapy to treat and rehabilitate injuries of disabled weightlifters - Dhafir Harb Ewajela Al-Ibraheemi,; Abdulkhliq Alhasan, Ahmed Muhammad; Abdulhassan, Ghassan Adeeb (International Journal of Psychosocial Rehabilitation, 2020)
Aquatic therapy is predominantly used for getting relaxation when the athletes are injured and lost their energy to do the practice in the workout sessions. Aquatic therapy can be provided to the athletes privately or in the rehabilitation centers. The previous research studies have revealed that the power of aquatic therapy is much faster than general physiotherapy treatments. In this article the aquatic therapy is experimented on the injured weightlifters and disabled weightlifters to provide the relief and revival strength. The paper has illustrated the possible aquatic therapy treatments and how they are going to provide the relief and strength to the injured patients to gain muscle strength and pain relief. The paper also suggested the most suitable aquatic therapy methods to the weightlifters to get the relief and revival strength. Aquatic therapy can provide not only physical relief but also neurological relief to he injured and disabled athletes.